Taxonomy of European Damaeidae VIII. Contribution to classification of genus Damaeus C. L. Koch, 1835, with a review of Adamaeus Norton, 1978 and Paradamaeus Bulanova-Zachvatkina, 1957 and redescription of three species - Miko, Ladislav (Zootaxa, 2015)
Adamaeus Norton, 1978 and Paradamaeus Bulanova-Zachvatkina, 1957, two subgenera of genus Damaeus C. L. Koch, 1835, are reviewed on the basis of the redescription of their type species. Subgenus Eudamaeus Pérez-Iñigo, 1987 and genus Tectodamaeus Aoki, 1984 are reviewed and their relation to Damaeus is discussed. Damaeus firmus Kunst, 1957 is redescribed and placed into the nominate subgenus. Damaeus helveticus (Schweizer, 1956) n.comb. is redescribed and placed into the nominate subgenus, its synonymy with Damaeus (Adamaeus) onustus C.L.Koch, 1844 is rejected. Damaeus alpinus (Schweizer, 1956) n.comb. is redescribed and placed into the nominate subgenus. Lectotypes and paralectotypes of Damaeus firmus Kunst, 1957; Damaeus helveticus (Schweizer, 1956) and Damaeus alpinus (Schweizer, 1956) are indicated. Based on published reviews and redescriptions, new diagnoses for Tectodamaeus Aoki, 1984, Damaeus C. L. Koch, 1835 and its subgenera are proposed, and a list of all known European species of Damaeus C. L. Koch, 1835 is provided. Tectodamaeus longus Xie & Yang, 2009 is newly combined to Damaeus as D. longus (Xie & Yang, 2009) n.comb.